Energy Efficiency and Reliability in Underwater Wireless Sensor Networks Using Cuckoo Optimizer Algorithm - M. Dosaranian-Moghadam; Z. Amo-Rahimi (AUT Journal of Electrical Engineering, 2018)
Energy efficiency and reliability are widely understood to be one of the dominant considerations for Underwater Wireless Sensor Networks (UWSNs). In this paper, in order to maintain energy efficiency and reliability in a UWSN, Cuckoo Optimization Algorithm (COA) is adopted that is a combination of three techniques of geo-routing, multi-path routing, and Duty-Cycle mechanism. In the proposed algorithm, by presenting a cost function in COA algorithm, a hop-by-hop method of route selection is performed using power consumption and energy content of the current node; while in Greedy Geographic Forwarding based on Geospatial Division (GGFGD) algorithm, data transfer is based on the closest route to a destination criterion. Simulation results show that despite the increase in path lengths and the resulting increase in propagation delay, the remaining energy of the UWSN increases using the proposed technique compared to GGFGD algorithm. Besides, we will show that while improving energy consumption, the number of paths found and, therefore, reliability of the network in the proposed method that uses duty-cycle mechanism are higher than the ones in GGFGD algorithm.